Changes in physical activity and sedentary behaviours from before to during the COVID-19 pandemic lockdown: a systematic review. Issue 1 (1st February 2021) - Stockwell, Stephanie; Trott, Mike; Tully, Mark; Shin, Jae; Barnett, Yvonne; Butler, Laurie; McDermott, Daragh; Schuch, Felipe; Smith, Lee
Abstract : Objective: In March 2020, several countries banned unnecessary outdoor activities during COVID-19, commonly called 'lockdowns. These lockdowns have the potential to impact associated levels of physical activity and sedentary behaviour. Given the numerous health outcomes associated with physical activity and sedentary behaviour, the aim of this review was to summarise literature that investigated differences in physical activity and sedentary behaviour before vs during the COVID-19 lockdown. Design, data sources and eligibility criteria: Electronic databases were searched from November 2019 to October 2020 using terms and synonyms relating to physical activity, sedentary behaviour and COVID-19. The coprimary outcomes were changes in physical activity and/or sedentary behaviour captured via device-based measures or self-report tools. Risk of bias was measured using the Newcastle-Ottawa Scale. Results: Sixty six articles met the inclusion criteria and were included in the review (total n=86 981). Changes in physical activity were reported in 64 studies, with the majority of studies reporting decreases in physical activity and increases in sedentary behaviours during their respective lockdowns across several populations, including children and patients with a variety of medical conditions. Conclusion: Given the numerous physical and mental benefits of increased physical activity and decreased sedentary behaviour, public health strategies should include the creation and implementation of interventions that promote safe physical activity and reduce sedentary behaviour should other lockdowns occur.